LAG-3 inhibits the activation of CD4+ T cells that recognize stable pMHCII through its conformation-dependent recognition of pMHCII. (December 2018) - Maruhashi, Takumi; Okazaki, Il-mi; Sugiura, Daisuke; Takahashi, Suzuka; Maeda, Takeo; Shimizu, Kenji; Okazaki, Taku
Abstract The success of tumor immunotherapy targeting the inhibitory co-receptors PD-1 and CTLA-4 has indicated that many other co-receptors might be potential druggable targets, despite limited information about their functional differences. Here we identified a unique target selectivity for the inhibitory co-receptor LAG-3 that was intrinsic to its immunoregulatory roles. Although LAG-3 has been reported to recognize major histocompatibility complex (MHC) class II, it did not recognize MHC class II universally; instead, we found that it selectively recognized stable complexes of peptide and MHC class II (pMHCII). LAG-3 did not directly interfere with interactions between the co-receptor CD4 and MHC class II or between the T cell antigen receptor and MHC class II. Instead, LAG-3 preferentially suppressed T cells responsive to stable pMHCII by transducing inhibitory signals via its intracellular region. Thus, LAG-3 might function more selectively than previously thought and thereby maintain tolerance to dominant autoantigens. LAG-3 is a co-inhibitory receptor on T cells, but its mode of action is controversial. Okazaki and colleagues demonstrate that LAG-3 preferentially binds stable MHC class II complexes and thereby selectively maintains tolerance of self-reactive T cells.